Q:

Name the postulate or theorem you can use to prove ADE=EBA?

Accepted Solution

A:
Answer:(c)  Δ ADE ≅  Δ EBA  by AAS TheoremStep-by-step explanation:Here, in Δ ACEAC  =  CE (given)Also, ANGLES OPPOSITE TO EQUAL SIDES ARE EQUAL.⇒ ∠E  = ∠A  ..... (1)Now, in Δ ADE and Δ EBA ∠E  = ∠A  (from above) ∠ADE  = ∠ABC ( right angle)  AE = AE (common side)hence, Δ ADE ≅  Δ EBA  by AAS TheoremAs,  by AAS Theorem (ANGLE ANGLE SIDE) Two triangle said said to be congruent if 2 angles and 1 side of one triangle is equal to 2 corresponding angles and 1 corresponding side of the other triangle.Hence, Δ ADE ≅  Δ EBA  by AAS Theorem